Social Protection in Transition Countries : Emerging Issues - Gupta, Sanjeev (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1996)
The paper discusses the social protection implications of the weakening financial and administrative capacity of countries undergoing economic transition. The formal sector is shrinking, and unemployment and underemployment are rising rapidly. This is affecting both the revenue base of social protection programs and the ability of these countries to target social benefits. These developments make it imperative for these countries to restructure social benefits, rely more on self-targeting mechanisms to deliver benefits, as well as take immediate steps to improve payroll tax compliance. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the author(s) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.